ISLAM NUSANTARA: Model of tolerance and integration of religious communities through the cultural traditions of Meroah Taon and Balit: Indonesian (Islamic) Model: Model of tolerance and integration of religious communities through the cultural traditions of Meroah Taon and Balit - Sepma Pulthinka (Jurnal Bimas Islam, 2023)
This study aims to analyze one of the Islamic traditions of the archipelago, namely meroah (Pepujan) taon and balit (Thanksgiving/selametan at the ancestral tomb) as a model of tolerance and integration that has been maintained by the Sasak Islamic community by bringing plantation crops is a form of harmonization of Man and nature intended as a forum for tolerance between Muslims and Buddhists Sasak Lombok. In line with the above, this study is of the view that culture is used as a relationship awareness oriented towards tolerance. the research method used is qualitative-analytic with entnographic approach that focuses on Islamic and Buddhist Sasak communities in Tegal Maja Village, North Lombok. Meroah taon and balit on the one hand is a ritual and on the other hand is a tool for social integration where groups can build social interaction and harmony between tribes. Nevertheless, this tradition is still maintained by the Sasak community who are Muslims and Buddhists. This is called by Islam Nusantara as a dialectic between local culture and Islamic values. Islam Nusantara appreciates the value of culture and Islam as a substantial thing to strengthen tolerance and social integration in a pluralistic society by containing the value of love, brotherhood and mutual cooperation between groups.